Best practices in the design and use of mobile applications: a systemic constructivist approach based on the overall mental health of adolescents - Ceberio , Marcelo R. (2025)
This article analyzes recent findings on the use of mobile applications (apps) for mental health in  adolescents from a systemic constructivist approach. Evidence regarding theirusefulness, limitations, and quality criteria is synthesized, emphasizing the need to establish best-practice principles that integrate clinical efficacy, safety, credibility, usability, co-design with young users, and ethical-cultural considerations. The analysis reveals a widespread absence of empirical validation in many available apps and proposes guidelines aimed at strengthening their role as a complement to traditional mental-health care strategies, framed within a global perspective and the paradigm of complexity.